Patrimonio arquitectónico en perspectiva geohistórica: La territorialización del noroeste de la provincia de Buenos Aires - Carrizo, Silvina Cecilia (2014)
The lack of studies about the northwest of Buenos Aires province in general, and regarding its architectural heritage in particular, encourages the exploration of this geographical area, dense of historical and material productions. This paper presents an analysis of the process of territorialization in the region. It considers the actions, products and architectural representations, from the mid-nineteenth to mid twentieth centuries. The main idea is to sharpen the technical and cultural view of the territory, enriching the vision of political and economic developments. Thus, this paper seeks to highlight the value of that architectural heritage.